2016
DOI: 10.1089/neu.2015.4140
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Residual Cortical and Subcortical Motor Evoked Potentials in Spinal Cord Injured Rats

Abstract: We have applied transcranial electrical stimulation to rats with spinal cord injury and selectively tested the motor evoked potentials (MEPs) conveyed by descending motor pathways with cortical and subcortical origin. MEPs were elicited by electrical stimulation to the brain and recorded on the tibialis anterior muscles. Stimulation parameters were characterized and changes in MEP responses tested in uninjured rats, in rats with mild or moderate contusion, and in animals with complete transection of the spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…These results preliminarily indicated that LFPEMF had a therapeutic effect on rats after SCI. To further investigate the therapeutic effect of LFPEMF, tcMMEPs, a widely used method to evaluate the recovery of electrophysiological function after SCI, were recorded weekly after surgery. Compared to the SCI group, tcMMEP latencies and amplitudes were significantly improved in the LFPEMF group from 2 to 8 weeks after surgery, which further suggested that LFPEMF could promote the recovery of neurological function in rats after SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results preliminarily indicated that LFPEMF had a therapeutic effect on rats after SCI. To further investigate the therapeutic effect of LFPEMF, tcMMEPs, a widely used method to evaluate the recovery of electrophysiological function after SCI, were recorded weekly after surgery. Compared to the SCI group, tcMMEP latencies and amplitudes were significantly improved in the LFPEMF group from 2 to 8 weeks after surgery, which further suggested that LFPEMF could promote the recovery of neurological function in rats after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of tcMMEPs, a form of MEP, involves a pair of Magstim 200 stimulators attached to a 50 mm diameter transducer coil. This apparatus has been widely used to evaluate the recovery of electrophysiological function after SCI, and the detection method has been described in our previous study . In brief, the transducer was positioned over the skull of the rat, and the single pin electrodes used to record EMG responses were placed into the hindlimb tibialis anterior muscle and gastrocnemius muscle of the rat.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the long-latency MEPs appear as a set of polyphasic waves of variable latency (15–22 ms), with a prominent peak at latency around 15 ms and mainly involves corticospinal tracts. Transecting the motor cortex or dorsal corticospinal tract abolishes most of the long-latency MEPs but spares the short-latency MEPs [1820]. Our result of reduced amplitude of short-latency MEPs indicates reduced excitability of reticulospinal tract in ChR2-YFP transgenic mice.…”
Section: Discussionmentioning
confidence: 67%
“…The first is a short-latency and high amplitude (~ 5 ms) response; the second is a long-latency (~15 ms), polyphasic wave that involves motor cortex and corticospinal tract [18, 19]. To specifically evaluate the long-latency MEPs, mouse motor cortex was electrically stimulated via an implanted screw.…”
Section: Resultsmentioning
confidence: 99%
“…We stimulated the left motor cortex and recorded the right tibia muscle. In intact recordings (2 days before SCI), every excitation elicited two separate waves, N1 MEPs and N2 MEPs [41]. N1 MEPs were single transcranial electrical pulses that were evoked with a short latency and recorded in the tibia anterior muscles in all of the animals that we tested.…”
Section: Functional Analyses Of the Adult Rat Contusion Model Of Spinmentioning
confidence: 99%